2022
DOI: 10.3390/fermentation8110596
|View full text |Cite
|
Sign up to set email alerts
|

Thermophilic Water Gas Shift Reaction at High Carbon Monoxide and Hydrogen Partial Pressures in Parageobacillus thermoglucosidasius KP1013

Abstract: The facultatively anaerobic Parageobacillus thermoglucosidasius oxidizes carbon monoxide to produce hydrogen via the water gas shift (WGS) reaction. In the current work, we examined the influence of carbon monoxide (CO) and hydrogen (H2) on the WGS reaction in the thermophilic P. thermoglucosidasius by cultivating two hydrogenogenic strains under varying CO and H2 compositions. Microbial growth and dynamics of the WGS reaction were monitored by evaluating parameters such as pressure, headspace composition, met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
0
0
1
Order By: Relevance
“…This result corresponds to 0.07 tons of H 2 produced per ton of steel mill gas (65 % CO, 15 % CO 2 ) or 100 % of the theoretical H 2 yield. Another study on the effect of high CO partial pressures, reported that the highest H 2 production rates were detected between 6 and 24 h of cultivation for the 50 % CO culture and between 24 and 48 h for the 75 % and 100 % CO culture (Díaz et al, 2022). However, in the current experiment (65 % CO), the highest H 2 production rates were observed at 24 h and thereafter they declined rapidly.…”
Section: H 2 and Vfas Production At 60 • Ccontrasting
confidence: 53%
“…This result corresponds to 0.07 tons of H 2 produced per ton of steel mill gas (65 % CO, 15 % CO 2 ) or 100 % of the theoretical H 2 yield. Another study on the effect of high CO partial pressures, reported that the highest H 2 production rates were detected between 6 and 24 h of cultivation for the 50 % CO culture and between 24 and 48 h for the 75 % and 100 % CO culture (Díaz et al, 2022). However, in the current experiment (65 % CO), the highest H 2 production rates were observed at 24 h and thereafter they declined rapidly.…”
Section: H 2 and Vfas Production At 60 • Ccontrasting
confidence: 53%